Design and Evaluation of Verapamil Hydrochloride Controlled Release Hydrogel-Based Matrix Tablets - Vidyadhara Suryadevara, Dr (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The present work was aimed to formulate Verapamil hydrochloride (HCl) an antihypertensive agent as controlled release (CR) matrix tablets using naturally occurring hydrophobic gum such as dammar gum as a polymer. Methods: In the present investigation, an attempt was made to induce hydrogel formation using polyelectrolytes such as calcium hydroxide and sodium hydroxide with the dammar gum in the presence of dissolution media and to extend the drug release up to 12 h. The hydrogels thus formed could be able to diffuse the drug through the channels present in the hydrogel-based matrix tablets. CR hydrogel-based matrix tablets were prepared using various concentrations of dammar gum, calcium hydroxide, and sodium hydroxide by wet granulation technique using isopropyl alcohol as a granulating fluid. The prepared tablets were evaluated for pre- and post-compression parameters. In vitro dissolution studies were performed in 0.1 N HCl for the first 2 h and in 6.8 pH phosphate buffer for next 10 h. Results: Among various formulations, dammar gum with calcium hydroxide and sodium hydroxide in the concentrations of 1 mg and 2.5 mg, respectively, were showed extended drug release up to 12 h in a steady state manner. The swelling index, Fourier transform infra-red, differential scanning calorimetry studies and scanning electron microscopy analysis were also performed on both the optimized formulations indicated that there were no drug and excipient interactions, and these formulations were found to be stable.